2020
DOI: 10.1007/s10021-020-00545-0
|View full text |Cite
|
Sign up to set email alerts
|

Peatland Wildfire Severity and Post-fire Gaseous Carbon Fluxes

Abstract: There may be differences between this version and the publisher's version. You are advised to consult the publisher's version if you wish to cite from this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…However, the ability for a peatland to recover the quantity of carbon lost within the fire return interval depends not only on the capacity to reinitiate soil organic carbon accumulation but also on the amount of carbon released through smouldering, closely tied to the hydrogeological setting (Ingram, Moore, Wilkinson, Petrone, & Waddington, 2019). Further, a warming climate regime may result in changes to the likelihood of high‐severity burns (Krawchuk et al, 2009), where burn severity may be a key control on the recovery time required for peatlands to transition back to C sinks post‐fire (Gray, Davies, Domènech, Taylor, & Levy, 2020), through limitation of evaporative water loss associated with burned surface hydrophobicity (Kettridge et al, 2015) and changes to the surface thermal regime (Morison, Petrone, Wilkinson, Green, & Waddington, 2020). Shortened fire cycles in the WBP (increase peatland fire frequency) will likely result in changes to the C biogeochemical function of low‐lying peatlands (Wieder et al, 2009), but the direction or magnitude of this change is relatively unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ability for a peatland to recover the quantity of carbon lost within the fire return interval depends not only on the capacity to reinitiate soil organic carbon accumulation but also on the amount of carbon released through smouldering, closely tied to the hydrogeological setting (Ingram, Moore, Wilkinson, Petrone, & Waddington, 2019). Further, a warming climate regime may result in changes to the likelihood of high‐severity burns (Krawchuk et al, 2009), where burn severity may be a key control on the recovery time required for peatlands to transition back to C sinks post‐fire (Gray, Davies, Domènech, Taylor, & Levy, 2020), through limitation of evaporative water loss associated with burned surface hydrophobicity (Kettridge et al, 2015) and changes to the surface thermal regime (Morison, Petrone, Wilkinson, Green, & Waddington, 2020). Shortened fire cycles in the WBP (increase peatland fire frequency) will likely result in changes to the C biogeochemical function of low‐lying peatlands (Wieder et al, 2009), but the direction or magnitude of this change is relatively unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches for burn severity evaluation [25], based on fire effects on the soil compartment, have already shown the capacity of visual indicators and Composite Burn Index (CBI) values to reflect changes in soil biophysical properties. Indeed, several studies [89][90][91] have revealed that using individual visual indicators, such as soil organic depth, together with semiquantitative metrics, such as the CBI, has proven to be useful in the assessment of other soil characteristics, such as changes in carbon storage after combustion. Future research should focus on developing accurate remote sensing methodologies that allow a better understanding of the integrated environmental impacts of forest fires on soils.…”
Section: Discussionmentioning
confidence: 99%
“…Even though wildfires occur much less frequently than prescribed burns, owing to their size and severity, they lead to far greater losses of C, including from peat. Finally, any assessment of burning impacts on carbon / GHG emissions must also consider methane fluxes, especially given the recent evidence that suggests low-severity fires may suppress peatland methane emissions (Davidson et al 2019;Gray et al 2020) and mowing or unmanaged sites might emit far more methane (Heinemeyer et al 2019c).…”
Section: Habitat State Of Peatlands -Favourable Vs Unfavourable Condition (Degraded Modified Intact State)mentioning
confidence: 99%